Pharmacotherapeutic efficacy of gel Kvotlan in the treatment of trophic ulcers of venous ethiology - A. N. Plekhanov; O. A. Shabatina (Acta Biomedica Scientifica, 2015)
Authors of given article conducted an estimation of pharmacotherapeutic efficiency of gel Kvotlan in the treatment of long-to-heal trophic ulcers of venous ethiology. 32 patients with venous trophic ulcers were included in the analysis of case records. There were 12 (37,5%) men and 20 (62,5%) women among them. The age of patients varied from 32 to 69 years. A preparation applied in the form of gel in a combination with gauze wad once a day, putting on ulcer wound interface. Treatment took 21 day. Application of Kvotlan on wound interface stimulated macrophagal reaction, strengthened proliferation of fibroblasts and epithelial, reduced degree of bacterial contamination of trophic ulcer. Clarification of ulcers from fibrin presence was reached by 15,2 days from an start of treatment. Along with clarification of wound interface there was a considerable decrease in a painful syndrome and also reduction of degree of discomfort. Kvotlan has expressed antibacterial and antioxidant effects. Besides, gel has expressed recycling and wound healing properties in comparison with comparison preparations. High percent of recovery of patients after one course of treatment and low level of relapses allow to recommend gel application of Kvotlan in complex therapy of trophic ulcers in case of chronic venous insufficiency diseases.